The impact of changes in temperature and precipitation on tourists arrival: An ARDL analysis for the case of a SIDS. Issue 19 (1st October 2020) - Fauzel, Sheereen
ABSTRACT: This paper examines the long-run and short-run impact of changes in temperature and precipitation on tourist arrivals in Mauritius. In this study, the bounds testing approach to cointegration is used. The autoregressive distributed lag model is applied on yearly time series data over the period 1980–2017. The main findings show that precipitation level as proxied by rainfall negatively affect tourist arrivals in both the short run and long run while the temperature is an insignificant factor. Moreover, an increase in the income of tourists and hotel rooms availability is seen to increase tourist arrivals. However, high domestic prices discourage tourists from visiting the island. The findings further confirm the stability of the model for the small island developing state of Mauritius.